Importance of the sector policy in the business management of the state electricity service in rural areas of Peru - Arellán Yanac, Luis Alberto (2021)
Currently, the urgency of the Peruvian government arises to decree sectoral policies to provide optimal and efficient distribution of electricity service and thus improve the quality of life of the rural population, one of these distributors is the company Electrocentro SA, owned by the State in the rural area, where it is known that the projects are not very profitable due to the geographical conditions of the place. Therefore, it is important to understand the relationship that these policies have on the management of the state-owned company. The result of this research shows the significant relationship that still exists around the electrification policy for the administration of the state electricity distribution company in two main stages, which are planning and organization. Thus, a sectoral policy becomes important to the extent that it can be considered to improve the administrative management of electric power distribution companies in rural areas of the country. The methodology used is descriptive, applied and correlational, because the phenomenon studied will be described by a current situation and each variable is reviewed by the theoretical framework.